Effect Of Long Thawing On The Quality Of Frozen Cow Brahman Cattle - Ririn Novita; Hayatun Novrida; Sri Lestari (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This study purposed is to determine the effect of thawing duration toward the quality of Brahman frozen semen. These include the motility of Spermatozoa, Spermatozoa concentration, Percentage of Spermatozoa Viability, Percentage of Spermatozoa Abnormalization and Individual Moitility, which was conducted at the UPTD Balai Artificial Insemination (BIB) Sembawa, Banyuasin District, South Sumatra Province. This research is experimental and carried out a non-factorial complete random design analysis (CRD) consisting of 6 levels of treatment and 4 repetitions so that 24 unit experiments are be obtained, through variations in the treatment of 10, 20, 30, 40, 50, and 60 seconds, the length of time thawing. The effect of frozen thawing semen for Brahman Cattle has a very significant effect on Individual Motility and Percentage of Viability of Spermatozoa. Thawing time of 30 seconds on T3 treatment gives a very good influence on the quality of frozen semen of Brahman Cows, while on thawing time of 50 seconds on T5 treatment gives good quality on the percentage of spermatozoa abnormalities. The frozen semen spermatozoa concentration value of Brahman cattle is 53 x 106 Keywords: quality of frozen semen, thawing duration, Brahman cattle